Contributors and associated risk factors of neonatal mortality in a tertiary care hospital in the sub-Himalayan region of West Bengal - Bagchi, Nilay Ranjan (International Journal of Contemporary Pediatrics, 2022)
Background: Lack of revision of knowledge on the magnitude of problem, cause and factors associated with neonatal mortality hampering early interventions and thus preventing reduction of neonatal mortality rate in India. Neonatal mortality statistics are sensitive indicators of the utility, convenience and effectiveness of maternal child health service in the community. This study was done to see the mortality pattern of neonates and contributing factors at the special newborn care unit (SNCU) and neonatal intensive care unit (NICU) of a rural tertiary care hospital so that special attention to those cause and factors can lead to favourable outcomes. Methods: This was a cross sectional retrospective study done in the SNCU and NICU of rural tertiary care centre of West Bengal for a period of three years with neonates admitted before 28 days of life. Data were collected in pre-designed proforma by analysing the case sheets from the records section of the hospital. Results were analysed by descriptive analytical method. Results: Total 13738 babies were admitted in the study period (7143 inborn and 6595 outborn). Majority of the inborns (86.8%) and outborns (68.4%) were discharged during that period while 9.4% inborns and 19.5% outborns were expired and only those expired cases were included in this study. HIE/moderate-severe birth asphyxia (41.2%) was the major contributor of death in inborns but in outborns the most common contributor of death was sepsis/pneumonia/meningitis (34.8%). Prematurity and low birth weight were the most common associated risk factors in both the groups. Conclusions: This study delineating the mortality patterns and associated risk factors of neonates in a rural tertiary care hospital of West Bengal which is unique in its kind. Outcome analysis showed that neonatal mortality rate for outborn babies was higher than in relevant recent studies.